The Organizational Climate and its Diagnosis a Conceptual Approximation - García Solarte, Mónica (Cuadernos de Administración, 2009)
The organizational climate is now a key factor in business development, and thorough study, diagnosis and improvement directly affects the so-called spirit of the organization. It is for this reason that this paper makes a conceptual approach, since different authors, which helps to highlight the importance of climate in organizational changes, and outlines the various tools that can be used for measurement and diagnosis and consider many variables that revolve around the organization's values, beliefs, customs and business practices, and clarifying the causes of satisfaction and dissatisfaction at work, and thus the incidence of these in the organizational changes